2006
DOI: 10.1159/000093300
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Energy Protection of Ischemic Preconditioning on Hepatic Ischemia/Reperfusion Injury in Rats

Abstract: Background: Hepatic ischemia/reperfusion (IR) injuries associated with hepatic resections are unresolved problems in the clinical practice. The aim of this study is to elucidate the effect of ischemic preconditioning (IPC) on the energy charge (EC) and related mechanisms at the late phase of hepatic IR injury. Methods: 30 Wistar rats were randomly divided into sham, IR and IPC groups. The model of partial hepatic IR was used. The rats were subjected to 60 min hepatic ischemia, pretreated by IPC (10/15 min) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
5
9
0
Order By: Relevance
“…In the present study, I/R caused significant increases in the hepatic malondialdehyde levels, end products of lipid peroxidation. This observation is in agreement with the previous studies, where elevated levels of lipid peroxidation products were increased from 40 to 80% above basal values [33][34][35] . Lipoic acid treatment abolished the increase in malondialdehyde, probably in part by scavenging the very reactive hydroxyl and peroxyl radicals.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, I/R caused significant increases in the hepatic malondialdehyde levels, end products of lipid peroxidation. This observation is in agreement with the previous studies, where elevated levels of lipid peroxidation products were increased from 40 to 80% above basal values [33][34][35] . Lipoic acid treatment abolished the increase in malondialdehyde, probably in part by scavenging the very reactive hydroxyl and peroxyl radicals.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, I/R caused significant increases in the hepatic malondialdehyde levels, end products of lipid peroxidation. This observation is in agreement with the previous studies, where elevated levels of lipid peroxidation products were increased from 40% to 80% above basal values (Sener et al, 2003;Ofluoglu et al, 2006;Zhu et al, 2006). Furthermore, our results demonstrated that GSE treatment abolished these increases in malondialdehyde, probably in part by scavenging the very reactive hydroxyl and peroxyl radicals.…”
Section: Discussionsupporting
confidence: 93%
“…Considerable evidence suggests that oxygen derived free radicals are involved in the hepatic injury caused by ischemia and reperfusion (Sener et al, 2003(Sener et al, , 2005Ofluoglu et al, 2006;Zhu et al, 2006). Thus, therapeutic strategies are designed to reduce free radicalinduced damage, either by intervening in the process by which free radicals are formed or by scavenging the free radicals that have already been formed.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in agreement with the previous studies, where elevated levels of lipid peroxidation products were increased from 40% to 80 above basal values [23][24][25]. Furthermore, our results demonstrated that leaves of Myrtle Black fruit treatment can inhibit the production of oxygen radicals and prevent them from injury to liver tissue.…”
Section: Liver Ischemia-reperfusionsupporting
confidence: 94%